LIFE OF ANGAMI WOMEN IN THE TRADITIONAL SOCIETY - Kire, Sedevinuo; Keyho , Khruvolu (International Journal of Research -GRANTHAALAYAH, 2024)
The Angami are a major tribe in Nagaland, a land made up of a conglomeration of many tribes, each tribe is distinct in its own character. Traditionally Angami society was centered on warfare, this war culture promotes a patriarchal society and male dominance was the norm, with a self-governing system. Women as a daughter, sister, wife, and mother were assigned enormous role. A girl child was segregated from male child and was prepared for her marriage from her childhood as the society required women of very high moral standard, for these teachings of girl or women were not neglected and also for self-sufficiency and independent life. The main objective of this paper is to study and explore the lives of women in the traditional Angami society . As a qualitative study, data were employed through primary and secondary sources. Today, the conservative view has slackened and her status and role is not only related to her family but education and career while continuing many of their traditional family obligations. She is responsible for the economy and sustainability of her home and community. This paper does a simple study from a women’s perspective since the life, value worth importance of a woman in all walks of life are kept in the dark or is invisible while writing the history of certain people.